Assessing Citizens’ Readiness and Utilization of the National Scam Response Centre (NSRC) in Combating Online Scams: The Moderating Effect of Education (Architecture Image Studies, 2025)
The increasing prevalence of online scams poses significant threats to financial security, trust in  digital systems, and national economic stability. To address this growing concern, Malaysia established the National Scam Response Centre (NSRC) as a centralized platform for scam reporting and intervention. Despite the NSRC’s potential, limited empirical research has examined factors influencing its utilization. This study investigates the impact of citizens’ readiness factors including awareness, perceived risk, performance expectancy, effort expectancy, and social influence on NSRC utilization, while also examining the moderating role of education. Drawing upon Protection Motivation Theory (PMT), Perceived Risk Theory (PRT), and the Unified Theory of Acceptance and Use of Technology (UTAUT), a survey was administered to 416 respondents across Malaysia. Partial Least Squares Structural Equation Modelling (PLS-SEM) was employed for data analysis. The results reveal that all five readiness factors significantly influence NSRC utilization, with awareness being the strongest predictor. Education was found to significantly moderate the relationship between awareness and utilization but did not moderate other predictors. The findings underscore the importance of enhancing public awareness and digital literacy to strengthen citizen engagement with NSRC services